THE CONSTRUCTION OF THE IDENTITY OF "PARIAH" IN PEREGRINACIONES DE UNA PARIA (2003) BY FLORA TRISTÁN - Calderón Muchotrigo, Estefany (2019)
The present work focuses on the work Peregrinaciones de una paria de Flora Tristán with respect to the process of construction of "outcast" in the subject. For this, we will need to focus on the position that women occupy in the 19th century, both in the Peruvian and international context. Likewise, we will analyze the different textual marks that reveal the category of "pariah" not only in terms of her illegitimate daughter status or her status as an intellectual woman but also in the opinions that are governed in a traditional society. Finally, we will see that there are three phases for the formation of the pariah identity: the beginning, the reaffirmation and the dispossession.